2016
DOI: 10.1021/acschembio.6b00081
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Riboswitches and Ribozymes Potently Activate the Human Innate Immune Sensor PKR

Abstract: The innate immune system provides the first line of defense against pathogens through the recognition of non-specific patterns in RNA to protect the cell in a generalized way. The human RNA-activated protein kinase, PKR, is a dsRNA binding protein and an essential sensor in the innate immune response, which recognizes viral and bacterial pathogens through their RNAs. Upon activation via RNA-dependent autophosphorylation, PKR phosphorylates the eukaryotic initiation factor eIF2α leading to termination of transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…Z-like steps were further identified in single stranded RNA 5′ -triphosphate groups ( 5′- PPP-RNA), a signature of viral RNA, when recognized by interferon-induced proteins with tetratricopeptide repeats of the IFIT5 family. Three crystal structures of the human IFIT5 protein in complex with 5‘- PPP-N 1 N 2 N 3 N 4 (N = C, U or A) ligands (Figure 8 ) ( 70 72 ) reveal that the ligand is recognized in a non-sequence- but conformation- and modification-specific manner. Indeed, no nucleobase-to-protein contacts are observed in these structures but only contacts to the ribose-phosphate backbone and the binding pocket of this protein does not seem large enough to accommodate the usual capping modifications found in eukaryotic RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Z-like steps were further identified in single stranded RNA 5′ -triphosphate groups ( 5′- PPP-RNA), a signature of viral RNA, when recognized by interferon-induced proteins with tetratricopeptide repeats of the IFIT5 family. Three crystal structures of the human IFIT5 protein in complex with 5‘- PPP-N 1 N 2 N 3 N 4 (N = C, U or A) ligands (Figure 8 ) ( 70 72 ) reveal that the ligand is recognized in a non-sequence- but conformation- and modification-specific manner. Indeed, no nucleobase-to-protein contacts are observed in these structures but only contacts to the ribose-phosphate backbone and the binding pocket of this protein does not seem large enough to accommodate the usual capping modifications found in eukaryotic RNAs.…”
Section: Resultsmentioning
confidence: 99%
“…56 We found that all of these bacterial RNAs activate PKR under both human and bacterial physiological magnesium conditions with remarkably high potency considering their complex structures. Maximal PKR activity ranged from 80–140% that of long dsRNA, requiring just 5–10-fold higher RNA levels.…”
Section: Bacterial Rna Activates Innate Immunity Via Pkrmentioning
confidence: 88%
“…This suggests that PKR does indeed dimerize on the tertiary structures of intact functional bacterial RNAs, leading to its activation. 56 These are among the first reports of RNAs that activate PKR via their tertiary structure. 57 …”
Section: Bacterial Rna Activates Innate Immunity Via Pkrmentioning
confidence: 95%
“…Post-transcriptional regulation, including alternative polyadenylation, splicing, localization, and degradation has received less attention, but also can substantially impact mRNA abundance (Floris et al 2009;Walley and Dehesh 2010;Feng et al 2015;Kawa and Testerink 2017;Wong et al 2017;Gu et al 2018;Sorenson et al 2018). Changes in mRNA secondary and tertiary structures influence post-transcriptional processes (Bevilacqua et al 2016), as revealed by many examples based on in depth analysis of specific transcripts (Zaug and Cech 1995;Hull et al 2016). More recently, techniques have become available to query mRNA structure in vivo and genome-wide (Ding et al 2014;Rouskin et al 2014;Talkish et al 2014;Wan et al 2014), which allows the possibility to elucidate general principles underlying relationships between mRNA structure, post-transcriptional regulation, and transcript abundance.…”
Section: Introductionmentioning
confidence: 99%